Organizational Issues of Biomass Use Integrated Into the Short Supply Chain - Antal, Sándor; Vincze, Judit (Journal of Central European Green Innovation, 2021)
It is indisputable that by the first decades of the 21st century, waves will begin to collide over the heads of our globalized world. We have to answer specific questions that fundamentally determine the survival of our society, the quality of life of future generations. The correct answer to these questions is complicated by the fact that the individual dilemmas cannot be separated into independent sub-areas, they are interconnected on thousands and thousands of threads. We cannot manage the content of operational programs that respond to environmental, economic and social challenges in isolation. In addition, however, sustainability is a common denominator that can create consonance among the factors that will determine our near future. In the light of the above, it is also not a question of whether the world and domestic agriculture will face new challenges in the coming decades. In addition to the implementation of healthy and economical food production inherited from the past, the task of the production of natural industrial raw materials and the production of energy sources will also be connected with the same specific weight. However, the implementation of all this is not possible without the realization of multifunctional agriculture, which creates an opportunity to develop and introduce innovations that will enable agriculture to fulfill its “obligation”. In connection with all this, we explored the importance of biomass for economic and rural development, as well as the competitiveness of production. Based on the results, we proposed a system of plans and tools that can promote the efficient use of biomass for rural development.